The Study of Human Resources Management Practice on Corporate Social Responsibility - Manurung, Arifin Hasudungan; Riyanto, Setyo; Pangaribuan, Hisar; AR, E. Nurzaman; Sunarsi, Denok (Program Pascasarjana Universitas Negeri Makassar, 2021)
The topic of corporate social responsibility and human resource strategy has developed together in the study as well in practice in a business environment. Both have become very powerful tools within the company to achieve sustainable growth for the company. Corporate social responsibility deals with labor-related issues, such as human rights, labor practices, health care, and the environment, and others, while implementing a good human resource strategy will support the practice of corporate social responsibility to be more effective, meaning that there is a mutual relationship among them. Companies that implement corporate social responsibility properly will pay attention to efforts to work legality at the company and improve company performance and more adequate business sustainability. This research has shown that adequate human resources management practice would significantly increase the company's corporate social responsibility.